Gleason grading of prostate cancer : a contemporary approach - Amin, Mahul B. (LWW medical book collection., 2004)
Featuring more than 300 full-color photomicrographs that represent the entire spectrum of the Gleason grading system, this atlas is the first comprehensive and definitive reference devoted to Gleason grading of prostate cancer. It is written by four eminent authorities in urologic pathology who bring their collective expertise and consensus opinion in Gleason grading. Illustrative case examples from the authors' collections highlight the pitfalls and problems of applying the Gleason grading system to contemporary techniques in pathology.